Morphological, Molecular, and Growth Characteristics of a Cryptic Species, Strombidium parasulcatum n. sp. (Alveolata: Ciliophora: Oligotrichida) - Tsai, Sheng-Fang; Lee, Meng-Lun; Chiang, Kuo-Ping (Frontiers in Microbiology, 2022)
A new marine planktonic ciliate from Taiwan, Strombidium parasulcatum, is described based on live observations, protargol staining, and molecular data. Its morphological characters are similar to those of S. sulcatum Claparède & Lachmann, 1859 (sensu Song et al., 2000); but differ from S. sulcatum (sensu Fauré-Fremiet, 1912 and sensu Fauré-Fremiet and Ganier, 1970) by several morphological characters. The 18S rDNA sequences of the two forms display 76 base pair differences (about 5%), indicating that they should be considered separate species. The highest observed specific growth rates of S. parasulcatum in culture were 1.79 d-1 over 1 day and 1.52 d-1 over 2 days, both starting at day 5. Bacteria appear to be an important food resource for the cultivation of this medium-sized oligotrich ciliate. This and other recent studies suggest that cryptic species may be common in the genus Strombidium, and an integrative approach including morphological, ecological, and molecular data should be used to address this question.